2020
DOI: 10.24843/eeb.2020.v09.i11.p01
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND AWARENESS DAN PURCHASE INTENTION (Studi Kasus : SMK Kesehatan Sanjiwani Gianyar)

Abstract: This study examined influence of social media marketing on brand awareness and purchase intention. SMK Kesehatan Sanjiwani Gianyar conducts social media marketing through paid promotions on Instagram and Facebook to increase brand awareness and interest of junior high school students to attend SMK Kesehatan Sanjiwani Gianyar. Data of 2017-2019 shows a decrease in the number of students, even though paid promotions have been carried out through Facebook and Instagram. Method in this study was Structural Equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 2 publications
5
12
2
9
Order By: Relevance
“…Social media significantly influences purchasing intention, according to research by Kuspriyono and Nurelasari (2018), Balakrishnan, et al (2014), Priatni, et al (2020), and Putri's Research Results (2016. The findings of this study, however, conflict with those of Putra & Aristana's (2020) study, which found that social media had no discernible impact on purchase intention.…”
Section: Because Everyone Can View What Other People E Issn 2621-749xcontrasting
confidence: 99%
“…Social media significantly influences purchasing intention, according to research by Kuspriyono and Nurelasari (2018), Balakrishnan, et al (2014), Priatni, et al (2020), and Putri's Research Results (2016. The findings of this study, however, conflict with those of Putra & Aristana's (2020) study, which found that social media had no discernible impact on purchase intention.…”
Section: Because Everyone Can View What Other People E Issn 2621-749xcontrasting
confidence: 99%
“…Pada penelitian Putra & Aristana (2020) terdapat kesimpulan penelitian ini memiliki hasil SMM (Social media marketing) memberi pengaruh pada BA. Sejalan dengan hasil penelitian Priatni, Hutriana, & Hindarwati (2020) bahwa strategi promosi bisa bermanfaat untuk perusahaan yakni berbentk kesadaran dari pelanggan terhadap merek ataupun Brand awareness.…”
Section: The Environment (Social Media Marketing)unclassified
“…Minat beli adalah suatu proses perencanaan pembelian oleh seseorang terhadap suatu produk dengan mempertimbangkan beberapa hal, diantaranya jumlah produk, merek, dan sikap dalam mengkonsumsi produk tersebut [23], [24]. Minatbbeli dapat diidentifikasikan dengan indikator-indikator yaitu minat transaksional, minat referensial, minat preferensial, minat preferensial, minat eksploratif [25].…”
Section: Pendahuluanunclassified